Using Operational Dashboard for ArcGIS as A Solution for Monitoring of Public Street Lighting - Satria Wirabuana; Frederik Samuel Papilaya (Politeknik Negeri Batam, 2020)
Public Street Lighting (PSL) is a part of road complementary buildings installed on the left, right and/or in the middle of the road to illuminate the surrounding environment. PSLs in residential areas usually do not have a small amount, so it will be difficult if the supervision is done manually. Therefore, we need a system that can monitor and maintain PSL effectively and efficiently. This study aims to prove that the Operations Dashboard for ArcGIS (ODA) can be utilized in monitoring PSL based on Geographic Information Systems (GIS). This PSL monitoring system can be used by the government and private parties to conduct PSL maintenance activities more efficiently and effectively, by providing information about PSL in realtime through widgets contained in ODA, and with the help of a mobile application, Collector for ArcGIS (CFA) as a sensor replacement that functions to carry out data collection in the field. The results of this study indicate that ODA can be used to monitor PSL by showing information about the status, location, type, and number of PSLs damaged.